Overactive bladder in menopausal women – estimate treatment of antimuscarinic drugs - Pertyński, Tomasz; Wilamowska, Agnieszka (Menopause Review/Przegląd Menopauzalny, 2007)
Urinary incontinence is estimated to affect over 5% of the adult population. It is defined by WHO as one of greatest medical problems of the 21st century. Urinary incontinence affects approximately 50 million adults in Europe and the United States. Overactive bladder (OAB syndrome) is defined by the International Continence Society as urgency, with or without urge incontinence, usually with frequency and nocturia. OAB affects approximately 50 million adults in Europe and the United States, with prevalence increasing with age. Current therapy consists primarily of anticholinergic drugs. Muscarinic receptor antagonists such as tolterodine, oxybutynin, trospine, solifenacin and darifenacin are the mainstay of treatment for OAB. Muscarinic receptor antagonists have varying efficacy, safety, tolerability and side effects. The aim of this study is to present the current knowledge and opinions on pharmacological treatment of OAB in the menopausal period.